Horizontal skin traction in abduction in physiotherapy management of Legg–Calvé–Perthes disease - Modrzejewska, Elżbieta; Tomska, Natalia; Turoń-Skrzypińska, Agnieszka; Kacperczyk, Piotr; Kołban, Maciej (Journal of Education, Health and Sport, 2018)
Legg–Calvé–Perthes disease is one of the many types of avascular necrosis with etiologies that have not been clearly confirmed yet. It affects the hip joint and is more prevalent in boys between the ages of 3 and 10. The purpose of this paper is to present physiotherapy management of Legg–Calvé–Perthes disease (LCPD) with horizontal skin traction in abduction. The treatment can be either conservative or operative. In both the cases, appropriate rehabilitation must be performed to facilitate the child’s full recovery. The objective of the comprehensive treatment is to restore the shape of the affected head of femur. The entire course of the disease, from onset to resolution, may take as long as a few years. This article is intended as an effective guide to choosing suitable exercises in the given stage of treatment.